Karya Pola Langkah Tigo Dalam Tari “Tolun Hati” - Kumala, Siski Yanti; Osmond, Dony; Stevenson, Yan; Ariastuti, Idun (JURNAL ILMIAH NUSANTARA, 2025)
The dance work "Tolun Hati" was inspired by a cultural phenomenon in Jorong Taeh Bukik, Payakumbuh District, Lima Puluh Kota Regency, namely the Dabuih Tradition. Dabuih is one of the traditional arts in the form of games or performances that involve skills, physical strength, immunity and courage. The creator translated it into a group choreography that was performed at the Huriah Adam Performance Building, Padangpanjang Indonesian Arts Institute. The work, which is divided into three parts, was performed by seven female dancers, where the seven female dancers played the role of the male body. The make-up used is beautiful stage make-up. While the clothes used are shiny gray creative kurung clothes with black pants. The methods used in creating this work are data collection or field observation, data processing, literature study, exploration, movement arrangement, improvisation, formation and evaluation.